Siyasah Syariah dan Implikasinya terhadap Pembaruan Hukum Zakat di Indonesia - Nafi, Muhammad; al-Amruzi, Fahmi; Hakim, Budi Rahmat; Mahmudin, Mahmudin; Syarifuddin, Syarifuddin; Hikmaturruwaida, Hikmaturruwaida (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This study describes how sharia siyasah is carried out by Muslims in Indonesia. Of course, it cannot be separated from the history of Islamic law developing and becoming an important part of positive law in Indonesia. Efforts to promote Islamic law have been on the agenda of Muslims throughout history. The regulation on zakat is one of the long journeys of sharia siyasah in Indonesia. In its formation cannot be separated from the debates in the legislature and the executive, which necessarily affect the material in the regulations formed. This research method is qualitative, by conducting library research, using a philosophical approach and a statutory approach. The result of this research is that in the material, zakat regulation tends to follow the renewal of zakat law, by not being shackled to one school but preferring the concepts of takhayur and talfiq. Material on the subject of zakat, the principles of zakat management, mustahik zakat, and the object of zakat is proof that there is takhayur in the selection of zakat law in Indonesia. This is because the discussion in the legislature does not put forward fanatics in one school, and uses the concept of mâ lâ yudraku kulluhu lâ yutraku kulluhu.